Reflections on the Core Concepts of Physiology and Pharmacology - Joel Michael; Paul J. White (Pharmacology Research & Perspectives)
ABSTRACT Core concepts are “big ideas” that can play a number of roles in helping students master a particular discipline: (1) they may define the important content of a discipline, (2) serve as tools to help students gain a better understanding of the discipline, and (3) facilitate transfer of learning between topics in the discipline. The core concepts of Physiology and of Pharmacology have been defined, and their deployment as part of Physiology and Pharmacology pedagogy is well underway. Here we compare and contrast the core concepts of these two disciplines and suggest lessons that have been learned that might assist other disciplines in deploying core concepts in their discipline.